KESULITAN KEMAMPUAN BERFIKIR KREATIF DAN LOGIS SISWA KELAS V SD IT FADHILAH PEKANBARU - Chairun Nisa Fadila Nasution; Febrina Dafit (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to describe the difficulties in creative and logical thinking abilities of fifth-grade students at SD IT Fadhilah Pekanbaru and the factors influencing these difficulties. The study employed a descriptive qualitative approach involving four fifth-grade students with low creative and logical thinking abilities and one classroom teacher as research subjects. Data were collected through observation, interviews, documentation, and tests, and were analyzed using the Miles and Huberman model. The findings revealed that students experienced difficulties in creative thinking skills, including fluency, flexibility, and originality, as well as logical thinking skills, including clarity of thought, argumentation, abstraction, and reasoning. These difficulties were influenced by internal factors such as low learning motivation, lack of self-confidence, limited ability to understand problems, and difficulty explaining thought processes. External factors included learning environments and teaching methods that had not optimally supported the development of students' thinking abilities. Therefore, learning activities that encourage students to actively develop ideas, express opinions, and solve problems independently are needed.